2014
DOI: 10.1186/1472-6882-14-148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of astragalus injection on the TGFβ/Smad pathway in the kidney in type 2 diabetic mice

Abstract: BackgroundIn traditional Chinese medicine, astragalus injection is used to treat diabetic nephropathy (DN). The current study was conducted to determine the effects of astragalus injection on DN by assessing potential modulation of the transforming growth factor beta TGFβ/Smad signaling pathway.MethodsDiabetic, male KKAy mice, aged 14 weeks were randomly divided into a model group and an astragalus treatment group, while age-matched male C57BL/6J mice were selected as controls. The treatment group received dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Asperulosidic acid, a bioactive iridoid glycoside, can also exert renal protective effects by inactivating both TGF-β/Smad and NF-κB signaling pathways (Xianyuan et al, 2019). Similar therapeutic effects are also found in other studies with herbal medicines (Nie et al, 2014;Wan et al, 2014;Zhao et al, 2016). Targeting Smad3-dependent non-coding RNAs could be another therapeutic approach to treat renal fibrosis and inflammation (Figure 4c).…”
Section: Treatment Of Ckd By Targeting Downstream Tgf-β/smad Signalinsupporting
confidence: 62%
“…Asperulosidic acid, a bioactive iridoid glycoside, can also exert renal protective effects by inactivating both TGF-β/Smad and NF-κB signaling pathways (Xianyuan et al, 2019). Similar therapeutic effects are also found in other studies with herbal medicines (Nie et al, 2014;Wan et al, 2014;Zhao et al, 2016). Targeting Smad3-dependent non-coding RNAs could be another therapeutic approach to treat renal fibrosis and inflammation (Figure 4c).…”
Section: Treatment Of Ckd By Targeting Downstream Tgf-β/smad Signalinsupporting
confidence: 62%
“…Bge.) is capable of reducing albuminuria, improving renal function, and ameliorating pathological changes [ 29 , 30 ]. Burning bush ( E .…”
Section: Discussionmentioning
confidence: 99%
“…Astragalus (Huang Qi in Chinese), also named as radix astragali, is a TCM from Mongolian milkvetch or membranaceus milkvetch. A meta-analysis comprising 25 studies showed that Astragalus injection had more therapeutic effect in DN patients such as decreasing BUN, Scr, and urine protein and improving Ccr and serum albumin level [ 63 ], and rebalancing TGF- β /Smad signaling could be a potential mechanism to prevent DN in KK-Ay mice [ 64 ]. Astragalus may protect diabetic rats kidney mediated by downregulation of Tie-2 [ 110 ], and radix astragali was reported to upregulate c-met expression in human kidney fibroblasts to delay the progression of DN [ 65 ].…”
Section: Applications Of Tcm In Dnmentioning
confidence: 99%